Global Neurotrauma Surveillance: Are National Databases Overrated?; Comment on "Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries" - Marissa A. Boeck; Hussein Ssenyonjo; Olive C. Kobusingye (Kerman University of Medical Sciences, 2023)
Injuries are a public health crisis. Neurotrauma, a specific type of injury, is a leading cause of death and disability globally, with the largest burden in low- and middle-income countries (LMICs). However, there is a lack of quality neurotrauma-specific data in LMICs, especially at the national level. Without standard criteria for what constitutes a national registry, and significant challenges frequently preventing this level of data collection, we argue that singleinstitution or regional databases can provide significant value for context-appropriate solutions. Although granular data for larger populations and a universal minimum dataset to enable comparison remain the gold standard, we must put progress over perfection. It is critical to engage local experts to explore available data and build effective information systems to inform solutions and serve as the foundation for quality and process improvement initiatives. Other items to consider include adequate resource allocation and leveraging of technology as we work to address the persistent but largely preventable injury pandemic.